Work plan for the Sustainable development working group (SDWG) 2001-2002. Annex 2. - Sustainable Development Working Group (SDWG) (Arctic Council Secretariat, 2001)
Annex 2 to the Arctic Council working group Sustainable Development Working Grouop (SDWG)'s work plan for the years 2001-2002, approved at the Senior Arctic Officials meeting in Rovaniemi, Finland, June 12-13 2001.